Insulin and rabbit anti-insulin receptor antibodies stimulate additively the intrinsic receptor kinase activity. - Ponzio, G (1987)
This paper describes the properties of rabbit polyclonal antibodies directed against purified human insulin receptor which strongly stimulate the intrinsic tyrosine kinase activity. The stimulatory effect of the antibodies on the kinase activity was obtained on the insulin receptor autophosphorylation as well as on the kinase activity towards a synthetic substrate. This stimulation is additive to that induced by insulin. Moreover, rabbit antibodies do not impair insulin binding. These data strongly suggest that antibodies and insulin act through separate pathways. This conclusion is reinforced by the differences observed on the phosphopeptide maps of the receptor's beta subunit whose phosphorylation was performed either in the presence of insulin or rabbit antibodies. Interestingly, these polyclonal antibodies can also induce an activation of the receptor autophosphorylation by interacting only with extracellular determinants. The anti-insulin receptor antibodies mimic insulin in their stimulatory effect on amino acid (AIB) uptake, but they have a different effect to that found on the kinase activity; the simultaneous addition of the antiserum and insulin failed to stimulate this amino acid transport over the level induced by a saturating concentration of hormone.